La medición de la inflación en España / Javier Ruiz-Castillo, Eduardo Ley, Mario Izquierdo - Ley, EduardoIzquierdo, Mario; Ruiz-Castillo, Javier (Estudios e Informes; 17)
Bibliografía: p. 344-351. Índices